2004
DOI: 10.2187/bss.18.206
|View full text |Cite
|
Sign up to set email alerts
|

Clustered DNA damage induced by heavy ion particles

Abstract: Clustered DNA damage (locally multiply damaged site) is thought to be a critical lesion caused by ionizing radiation, and high LET radiation such as heavy ion particles is believed to produce high yields of such damage. Since heavy ion particles are major components of ionizing radiation in a space environment, it is important to clarify the chemical nature and biological consequences of clustered DNA damage and its relationship to the health effects of exposure to high LET particles in humans. The concept of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…A common method to study these damages is to observe the conformational changes of the plasmid DNA. While an intact plasmid is supercoiled, conformational changes to relaxed circular or to linear fragments occur for a SSB or DSB, respectively (Boudaiffa et al, 2000;Terato and Ide, 2004). If more than one DSB is induced, fragmentation of the plasmid into short pieces takes place.…”
Section: Introductionmentioning
confidence: 99%
“…A common method to study these damages is to observe the conformational changes of the plasmid DNA. While an intact plasmid is supercoiled, conformational changes to relaxed circular or to linear fragments occur for a SSB or DSB, respectively (Boudaiffa et al, 2000;Terato and Ide, 2004). If more than one DSB is induced, fragmentation of the plasmid into short pieces takes place.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown in a recent review article by Terato [37], that  varies from around  = 0.006 DSBs/(MbpGy) [3,38,39] to  = 0.14 DSBs/(MbpGy) [40] for X-ray irradiation.…”
Section: Experimental Data and Discussionmentioning
confidence: 99%
“…It is well established that the level of clustering of DNA damage and their complexity increase with increasing LET of radiation (Terato and Ide, 2004;Sage and Harrison, 2011). For low-LET IR, this clustering occurs mainly on small sites of DNA and nucleosomes in the chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…High-LET radiation, such as α-rays, yields more than 90% of DSB with ends carrying additional single lesions (Terato and Ide, 2004;Hada and Georgakilas, 2008). It was shown that in the case of irradiation of cells with protons (LET 9.2 keV/m), 45% of the resulting SSB in the DNA are accompanied by additional damage of bases in close proximity to these breaks, and this value increases to 78% after exposure of these cells to α-particles (LET 129 keV/m) (Terato and Ide, 2004). Other studies have also shown the formation of more complex DNA lesions after exposure of cells to high-LET radiation (Semenenko and Stewart, 2004).…”
Section: Introductionmentioning
confidence: 99%